Exploring Factors Affecting Behavioral, Cognitive and Emotional Engagement of International Undergraduate Students in China 来华本科留学生学习性投入的影响因素研究——基于行为、认知和情感三维度 - Gong, Meiqiong; Cen, Yuhao (Journal of International Students, 2020)
Student engagement is one of the critical measures assessing the quality of international student education. This survey study examined the behavioral, cognitive and emotional engagement of international students at a research-intensive university on the east coast of China. The findings showed the interrelationship of the behavioral, cognitive and emotional dimensions of student engagement. The research revealed that individual characteristics had significant effects on emotional engagement, while having no effect on behavioral or cognitive engagement. Male students, first-generation students, and students enrolling in degree programs displayed a lower level of emotional engagement compared with their counterparts. The research also found that supportive campus environment and frequent student-faculty interactions were positively related to the three dimensions of student engagement, whereas peer interactions had no effect on any of the dimensions. 来华留学生的学习性投入水平，是衡量高校留学生教育质量的重要方式。本文将学习性投入划分为行为投入、高阶认知投入、情感投入三维度，基于中国东海岸一所研究型大学来华本科留学生的调查数据，对留学生的学习性投入水平与影响因素进行描述性统计与回归分析。研究发现，留学生三维度的学习性投入显著正相关。个人背景特征对留学生的情感投入存在显著影响，但对行为和高阶认知投入没有影响。男性、第一代大学生、攻读学位项目的留学生均呈现较低的情感投入。校园环境支持度和师生互动因素对学习性投入三维度都具有显著影响，但生生互动对学习性投入各维度没有影响。